Risk factors for fraud victimization: The role of socio-demographics, personality, mental, general, and cognitive health, activities, and fraud knowledge - Koning, Luka (International review of victimology, 2024)
Fraud against individuals is a major and growing problem. Understanding why some people fall victim to fraud, while others do not, is crucial in developing effective prevention strategies. We therefore studied the effect of socio-demographics, personality traits, mental, general, and cognitive health, routine Internet activities, and prior fraud knowledge on general fraud victimization, susceptibility to fraud attempts, and exposure to fraud attempts. We modeled data from a Dutch fraud victimization survey, using an exhaustive fraud taxonomy and a representative sample for which an elaborate set of historical background variables were available. Results show that there is no clear personality or other profile of those most at risk for fraud, except for having low self-control, having a non-Western, immigrant background or being a frequent Internet user. Improving fraud knowledge could be an effective way to prevent fraud victimization by reducing susceptibility to attempts.